Incorporating Media and Technological Literacy in the Social Studies Classroom - Nicolas Ciotola (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
So much has changed about the way we partake and receive our information over the last few decades. Seemingly everyone gets their information from the internet or television. Unfortunately, the internet allows for unchecked information to be taken as fact which leads to an incorrect interpretation of fact and fiction. There is arguably no greater target audience for the sort of misinformation found on the internet and social media than our youth due to how impressionable their minds are. Because of this, I am interested in discussing what can be done as social studies educators to prevent our students from falling prey to the plethora of misinformation that exists in our current technological and media world.